Impact of media: self-medication and the rising problem of antimicrobial resistance - Mahajan, Manali M.; Dudhgaonkar, Sujata (International Journal of Basic & Clinical Pharmacology, 2017)
Antimicrobial agents (AMAs) are one of the most commonly used as well as misused drugs. Antimicrobial resistance is an important growing global health issue which needs urgent addressal. Self-medication involves the use of medicinal products by the patient to treat self-recognized disorders, symptoms, recurrent diseases, or minor health problems. Medicines for self-medication are often called over the counter (OTC) drugs, which are available without a doctor’s prescription through pharmacies, mostly in the developing countries. Self-medication particularly with antibiotics has been widely reported, leading the World Health Organization to call attention to its dangers as a cause of antimicrobial resistance.